Camera, Action: Criminalisation and Authority in Public Surveillance - Heather M. Morgan (Sortuz)
This paper introduces and explores the use of social research methods, with some influence of gender scholarship, in relation to the interminable legal and social science ‘problem’ of how and why it seems that women commit less crime than men and how that imbalance occurs and remains relatively stable. Essentially, a summary of the background to and methodology of a current research project, which employs closed circuit television (CCTV) surveillance as the empirical lens of enquiry, is presented and discussed, along with some initial findings and observations, provoking questions of how and where else the criminal law has been and can be read, interpreted and practised. In particular, notions of subjectivity and authority as causes of criminalisation, as opposed to the criminal law itself, are considered. As a result of sociologically conceived field-based findings, this paper addresses concerns relevant to modern jurisprudence and so too implications for both policy and practice both in relation to the criminal law. The key reflection, however, is the use of qualitative methods, rooted in the social sciences, to address a legal research question: a matter of legal scholarship.